Filosofi Perkawinan Adat Sumba: Studi Komparatif Antara Teda dan Kan. 1055 §1 KHK 1983 - Umbu Zerri, Mario Venerial; Kapitan, Antonius; Panda, Herman Punda (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The oral tradition of teda is a culture prevalent in traditional marriages on Sumba Island. This research aims to explore the philosophy of traditional marriage of Sumba people through traditional poetry. The research method used is literature and comparative studies as well as in-depth interviews to obtain data on traditional poetry.It was found that the philosophy contained in traditional poetry is the principle of covenant, loyalty, sacredness, obtaining offspring and validity in front of many people. The results of this study can be a reference for anyone interested in exploring the traditional marriage of the Sumba community.